Educação ambiental como elemento da fronteira etnocultural: empoderamento e saberes dos povos indígenas Terena do Pantanal Sul - Souza, Edson Pereira de (2021)
When Luther brought up the philosophical phrase that “no one is forbidden to know more than the self”, he allowed me to associate with the dynamics of the original peoples, as they, since before the “discovery”, shared their knowledge with their generations. This proves the importance of sharing traditional knowledge, but historically numerous problems have compromised the perpetuation of this knowledge. Furthermore, based on conservation practices practiced by indigenous populations throughout history, I found the need for academia to provide more support and visibility to native peoples for the promotion and dissemination of their knowledge. It is this traditional knowledge that becomes practical actions in environmental education. Therefore, this thesis was built with the general objective of understanding environmental education as an instrument of the ethnocultural frontier amidst the dynamics of empowerment and production of traditional knowledge of the Terena peoples of the Pantanal Sul Region (Mato Grosso do Sul), in the which concerns the process of (re)occupation of (new) territories. And, in order to equate this work, methodologically we turned to a qualitative research, anchored in geographic and anthropological aspects, with a bias in ethnography. For this, observation techniques were used and, mainly, with the support of the Kozel Methodology for the interpretation of mental maps, which allowed the assessment of the view, of indigenous and non-indigenous people, over the Pantanal Sul region. representations expressed by social actors, it is possible to base the construction of the conceptual proposal of Ethnocultural Frontier, as well as the expression of the production of their traditional knowledge in the midst of historical and current actions in Environmental Education. Therefore, not from a finite perspective, but from the beginning of a reflexive search and possible debates for public policy proposals, especially for Environmental Education, one can find the transience of generations, especially with indigenous populations, based on their knowledge traditional threads.